Role of the Heart in Lactate Shuttling - Brooks, George A. (Frontiers in Nutrition, 2021)
After almost a Century of misunderstanding it’s time to appreciate that lactate shuttling is an important feature of energy flux and metabolic regulation that involves of a complex series of metabolic, neuroendocrine, cardiovascular and cardiac events in vivo. Cell-Cell and intracellular Lactate Shuttles in the heart and between the heart and other tissues fulfills essential purposes of energy substrate production and distribution as well as cell signaling under fully aerobic conditions. Recognition of lactate shuttling came first in studies of physical exercise where the roles of driver (producer) and recipient (consumer) cells and tissues were obvious. One powerful example of cell-cell lactate shuttling was the exchange of carbohydrate energy in the form of lactate between working limb skeletal muscle and the heart. The exchange of mass represented a conservation of mass that required the integration of neuroendocrine, autoregulatory and cardiovascular systems. Now, with greater scrutiny and recognition of the effect of the cardiac cycle on myocardial blood flow there brings an appreciation that metabolic fluxes must accommodate to pressure-flow realities within an organ in which they occur. Therefore, the presence of an Intra-cardiac Lactate Shuttle is posited to explain how cardiac mechanics and metabolism are synchronized. Specifically, interruption of blood flow during the isotonic phase of systole is supported by glycolysis and subsequent return of blood flow during diastole allows for recovery sustained by oxidative metabolism.